ANALISIS PERBEDAAN METODE PEMBELAJARAN KONVENSIONAL DAN ACTIVE LEARNING MAHASISWA AKUNTANSI UNIVERSITAS CIPUTRA: indonesia - Gunawan, Sherley; Santoso, Eko Budi; Mastan, Stanislaus Adnanto (Media Akuntansi dan Perpajakan Indonesia, 2020)
The purpose of this research is to find the difference between conventional learning method and active learning on accounting student Ciputra University batch 2018. Control method use PowerPoint and the experiment use reading guide and think group share. This research uses quasi experiment with post-test control group design, so it’s just look at the final result of the two classes. This research divides the respondents into two classes, 20 students on control class and 20 students on experiments class. This research using data from post-test by questionnaire with 10 questions multiple choice. The data analysis in this research use T-Test to see the difference between conventional learning method and active learning. The results of this research show that there is the differences in conventional learning method use PowerPoint and the active learning use reading guide and think group share with the average value of 82.50 for experiment class and 62.50 for control class and the significance value is 0.003 < 0.05 so that H1 is accepted and H0 is rejected.